2014
DOI: 10.1007/s11618-014-0556-8
|View full text |Cite
|
Sign up to set email alerts
|

Studious by association? Effects of teacher’s attunement to students’ peer relations

Abstract: We would like to express our gratitude to Chris Baerveldt and Tom Snijders for laying the foundation of this research by obtaining funds from NWO (grants 401-01-554 and 401-01-550, respectively). Data and R-scripts for replicating the reported analyses can be obtained on request from the authors. C. Steglich ()Abstract We study the role of teacher-perceived friendship on teachers' assessments of their students' learning efforts. Based on earlier studies, we expect that teacher-perceived friendship differs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…Consistent with previous findings (Dawes et al., 2017), teachers’ perceptions of students’ academic, social, and behavioral characteristics were associated with their attunement. Based on the association effect (Steglich & Knecht, 2014), we examined whether the academic, social, and behavioral characteristics of teacher‐perceived friends of the target student were related to teacher attunement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous findings (Dawes et al., 2017), teachers’ perceptions of students’ academic, social, and behavioral characteristics were associated with their attunement. Based on the association effect (Steglich & Knecht, 2014), we examined whether the academic, social, and behavioral characteristics of teacher‐perceived friends of the target student were related to teacher attunement.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that teacher‐perceived friendships lead to an overestimation of similarity among the students perceived as friends. This bias in teacher judgment has been reported for students’ externalizing behavior problems and academic orientation (Gest, 2006), academic expectations (Pittinsky, 2008), and study efforts (Steglich & Knecht, 2014). We expected a similar effect in teacher perceptions of bullying, victimization, and prosocial behavior.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations